Efektivitas Alat Permainan Edukatif (APE) Berbasis Media dalam Meningkatkan Kemampuan Berhitung pada Anak Kelas 2 di SDN 2 Wonotirto Bulu Temanggung - Ariyanti Ariyanti; Zidni Immawan Muslimin (Jurnal Psikologi Tabularasa, 2015)
This study aims to determine the effectiveness of the educational playing game based on media to improve numerical ability on second grade student at SDN Wonotirto, Bulu, Temanggung. The subject were 10 student, that divided into two groups, experimental group (5 students) and control group (5 students). They are second grade student at SDN Wonotirto, Bulu, Temanggung. The design of experiment which used is pretest and posttest control group design. The methods of data analysis techniques use Mann - Whitney U. The result of the data analysis showed a significant differences between post-test of experimental group and the control group with level of p = 0.032. It means there are differences numerical ability between the control group and the experimental group. The mean score of the experimental group after the treatment was given greater compared with the control group (7.5 3.5). So, educational playing game based on media is effective to improve the numerical ability